2020
DOI: 10.1186/s12864-020-6605-1
|View full text |Cite
|
Sign up to set email alerts
|

Unblended disjoint tree merging using GTM improves species tree estimation

Abstract: Background: Phylogeny estimation is an important part of much biological research, but large-scale tree estimation is infeasible using standard methods due to computational issues. Recently, an approach to large-scale phylogeny has been proposed that divides a set of species into disjoint subsets, computes trees on the subsets, and then merges the trees together using a computed matrix of pairwise distances between the species. The novel component of these approaches is the last step: Disjoint Tree Merger (DTM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…While estimating phylogenies from unaligned datasets is very difficult for ultra-large datasets, there has been substantial progress over the last few years that suggests that dataset size is not likely to remain a significant impediment in the long term. For example, there are divide-and-conquer strategies for improving scalability of phylogeny estimation methods (e.g., TreeMerge ( Molloy and Warnow, 2019 ) and Guide Tree Merger ( Smirnov and Warnow, 2020 )) that do not require aligned sequence inputs and that could be used with any tree estimation method, including computationally intensive methods (e.g., Bayesian MCMC) or maximum likelihood estimation under complex models (e.g., the GHOST model ( Crotty et al, 2020 ) available in IQtree). These and future advances may make it feasible to estimate highly accurate trees from ultra-large datasets of unaligned sequences without burdensome computational requirements.…”
Section: Discussionmentioning
confidence: 99%
“…While estimating phylogenies from unaligned datasets is very difficult for ultra-large datasets, there has been substantial progress over the last few years that suggests that dataset size is not likely to remain a significant impediment in the long term. For example, there are divide-and-conquer strategies for improving scalability of phylogeny estimation methods (e.g., TreeMerge ( Molloy and Warnow, 2019 ) and Guide Tree Merger ( Smirnov and Warnow, 2020 )) that do not require aligned sequence inputs and that could be used with any tree estimation method, including computationally intensive methods (e.g., Bayesian MCMC) or maximum likelihood estimation under complex models (e.g., the GHOST model ( Crotty et al, 2020 ) available in IQtree). These and future advances may make it feasible to estimate highly accurate trees from ultra-large datasets of unaligned sequences without burdensome computational requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that scalable phylogeny estimation methods have suffered in the presence of sequence length heterogeneity, and phylogenetic placement may provide a more accurate alternative [13]. For example, the divide-and-conquer tree estimation pipeline GTM [24] could benefit by using BSCAMPP. BSCAMPP can facilitate the initial tree decomposition of GTM for better placement of shorter, fragmentary sequences into an initial tree containing the longer full-length sequences, potentially leading to better final tree estimation.…”
Section: Discussionmentioning
confidence: 99%
“…The gray partnership generation sequences are shown in Tables 3-5. The optimal sequence for SP, ST, and SSFR is x0 k k = 1, 2, ⋯ ⋯ , 7 [23]. The grey relational grade description in the grey relational analysis demonstrates how the seven sequences (x0 k and xi k , if = 1, 2) are related to the grade, 7, k = 1, 2, 7 [24].…”
Section: Methodsmentioning
confidence: 99%